2015
DOI: 10.2135/cropsci2014.12.0816
|View full text |Cite
|
Sign up to set email alerts
|

Variation among Cowpea Genotypes in Sensitivity of Transpiration Rate and Symbiotic Nitrogen Fixation to Soil Drying

Abstract: Cowpea (Vigna unguiculata L. Walp.) is often considered a crop species appropriate for drier environments. However, little or no information exists on two key physiological traits for drought conditions: early decrease in transpiration rate in the soil drying cycle and sustained N fixation activity under low soil‐water conditions. In this study, the responses of these two traits to soil drying were compared among 10 genotypes. The fraction of transpirable soil water at which transpiration rate began to decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
0
19
1
Order By: Relevance
“…Measurement of TR and N 2 fixation activity in response to soil drying was achieved by following the protocol established by Sall and Sinclair (1991) and recently described by Devi and Sinclair (2013) and Sinclair et al (2015). One or 2 d before the dry‐down experiment was to begin, acrylic lids were attached to the pots and sealed around the base of the plant stem.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of TR and N 2 fixation activity in response to soil drying was achieved by following the protocol established by Sall and Sinclair (1991) and recently described by Devi and Sinclair (2013) and Sinclair et al (2015). One or 2 d before the dry‐down experiment was to begin, acrylic lids were attached to the pots and sealed around the base of the plant stem.…”
Section: Methodsmentioning
confidence: 99%
“…Two lines were identified that outperformed commercial checks under water deficit, but trade-offs were apparent under high-yielding conditions. In a glasshouse experiment comparing the normalised acetylene reduction activity of 10 cowpea lines in response to soil drying, the fraction of transpirable soil water at which N 2 fixation rate began to decline was 0.33 in the most sensitive line, whereas in another line there was no decline in N 2 fixation rate (Sinclair et al 2015). Whereas the sensitivity to water deficit in legume N 2 fixation is recognised, intra-specific variation is significant and has putatively adaptive value.…”
Section: Water-and Nitrogen-related Traits Of Other Cropsmentioning
confidence: 96%
“…However, nitrogen fixation is extremely tolerant to soil drying in cowpea 35 . The incorporation of improved drought tolerance and nitrogen fixation traits into elite lines of grain legumes is anticipated to generate better yielding cultivars that can be grown on marginal land.…”
Section: Symbiotic Nitrogen Fixationmentioning
confidence: 99%